2004
DOI: 10.1111/j.1463-1326.2004.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of a long‐term, GLP‐1‐treated, insulin‐secreting cell line is improved by preventing DPP IV‐mediated degradation of GLP‐1

Abstract: Glucagon-like peptide-1 (GLP-1) is an important insulinotropic hormone with potential in the treatment of type 2 diabetes. However, the short biological half-life of the peptide after cleavage by dipeptidylpeptidase IV (DPP IV) is a major limitation. Inhibition of DPP IV activity and the development of resistant GLP-1 analogues is the subject of ongoing research. In this study, we determined cell growth, insulin content, insulin accumulation and insulin secretory function of a insulin-secreting cell line cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
(78 reference statements)
0
7
1
Order By: Relevance
“…Indeed, it has been reported that continuous GLP-1 stimulation results in desensitization of GLP-1R, which can subsequently reduce insulin secretion in response to GLP-1 in insulin-secreting cell lines (Widmann et al 1996;Green et al 2005). However, the expression of GLP-1R and GIPR in islets did not change in DPP-IV inhibitor-treated mice in the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…Indeed, it has been reported that continuous GLP-1 stimulation results in desensitization of GLP-1R, which can subsequently reduce insulin secretion in response to GLP-1 in insulin-secreting cell lines (Widmann et al 1996;Green et al 2005). However, the expression of GLP-1R and GIPR in islets did not change in DPP-IV inhibitor-treated mice in the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…Because dipeptidyl peptidase-IV (DPP-IV) is responsible for the degradation of GLP-1 (Kieffer et al, 1995), orally available inhibitors of DPP-IV have been developed for therapeutic use in T2DM. A number of in vitro and in vivo studies support the view that DPP-IV inhibition improves ␤-cell function by enhancing insulin secretion and augmenting ␤-cell proliferation (Burkey et al, 2005;Green et al, 2005). Human data also indicate DPP-IV inhibition contributes to better glycemic control ).…”
mentioning
confidence: 65%
“…Hence, GLP-1 is an excellent candidate for use as a prophylactic treatment for maintaining glucose homeostasis in diabetic patients and has been extensively investigated. The very short plasma half-life (less than 2 minutes in the circulatory system), however, limits its pharmacotherapy study and clinical application [ 9 11 ]. Dipeptidyl peptidase IV (DPP-IV)-mediated cleavage at Ala 8 of mature N-terminal GLP-1 results in the production of inactivated N-terminal truncated peptides, GLP-1(9–36) or GLP-1 (9–37).…”
Section: Introductionmentioning
confidence: 99%